Application of King’s Philosophy to Analysis of Community Problems in Nakhon Pathom Province - Saenphumi, Somchai; Theerak, Winakon (Dhammathas Academic Journal, 2022)
This research aim is 1) to disseminate the knowledge of the King’s Philosophy to volunteer groups and 2) to study the application of the King’s Philosophy and community empowerment to analyze problems within the community. Using qualitative research, the key informant was the volunteer group of the Phutthamonthon, Nakhon Chai Si, and Sampran districts, a total of 34 people selected by purposive sampling. Research tools include documentary research, focus group interviews, non-participant observation, and descriptive analysis. The study found that: 1. After training on applying the King’s Philosophy, especially the principle of "understanding, connecting and development”. They defined understandingas understanding the problems that arise in each community and the state of the community through clear information. The principle of connectingis visiting villages, asking about the problem’s condition, and sincerely coming to help with unconditional love. And the principle of development is that there is training at local learning centers. 2. The community problem analysis found that the volunteer groups of Phutthamonthon District and Sampran District considered the "waste problem" an urgent and important problem and could create activities under the volunteer group to solve the problem. Both areas face the same problem because they are adjacent to the capital city. And the Nakhon Chai Si District volunteer group voted for the “Tha Chin River encroachment problem” which is an urgent problem, and activities can be created under the volunteer group to solve the problem. Finally, found that the volunteer group was a group of people who had strengths in social capital. When organizing activities to increase community potential or to solve community problems in the future, it often receives good cooperation from government agencies.